Effect Of Anomin® Supplementation During Prepartum Period On Periparturient Disorders In Dairy Animals - Patel, S.B.; Patel , K.R.; Jethva, P.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted to determine the effect of prepartum supplementation of anionic salt mixture (Anomin®) on incidence of periparturient disorders in dairy animals of individual farmers under field conditions. Total 80 advanced pregnant animals were selected about to calve during the period from 1st March to 10th April and were divided equally into treatment and control groups. The animals in control group were fed with concentrate mixture, green fodder and dry fodder as per availability, whereas animals of treatment group were fed with additional anionic salt mixture (Anomin®) @ 100 gm/animal/day (50 gm each in the morning & evening) for 20 days before expected date of calving. The periparturient disorders compared between anionic salt (Anomin®) supplemented (treatment) and control group revealed reduced incidence of retention of foetal membranes (7.50 vs 17.50%), genital prolapse (2.50 vs 5.00%), milk fever (0.00 vs 2.50%) and metritis (0.00 vs 10.00%) in anionic salt supplemented group as compared to control group (overall 10 vs 35%). Serum concentrations of both calcium (10.73±0.21 vs. 10.26±0.26 mg/dl) and phosphorus 5.55±0.12 vs. 4.89±0.14 mg/ dl) at 6 hrs postpartum were higher in anionic salt (Anomin®) supplemented group than the control calving group, with significant difference in phosphorous levels only. The results depicted beneficial effect of anionic salt supplementation to advanced pregnant dairy animals in terms of reduced periparturient disorders and thereby better health and productivity.
Keywords: Anionic salt (Anomin®); Periparturient Disorders; Calcium; Phosphorus